A spell for saints and sinners - Carpenter, Emily, 1967- (Kensington Publishing Corp, 2026)
"In front of an elegantly shabby townhouse on a Savannah side street sits a hand-painted sign: Miss Edie, Psychic. Ingrid White inherited the house and business from her beloved grandmother, a local celebrity in town. But unless Ingrid can find a way to pay for crushing property taxes and mounting repairs, she's going to lose them both. Ingrid has faith in the homespun witchcraft Edie passed down to her, yet hope and clients are dwindling. . . . Until Sailor Loeffler's bachelorette party changes everything. Sailor is local royalty--part of the vast "Savannah Sauce" empire, beautiful and wealthy beyond imagining--and Ingrid's reading is so accurate that she becomes the bride-to-be's confidante. To keep that access and all the privileges it brings, Ingrid relies more and more on hexes and dark spells--using the baneful magic Edie always warned her against. As Ingrid works even riskier spells, she is drawn further into the Loefflers' inner circle and the obstacles in her path melt away. But is it witchcraft or other, more earthbound forces? Ingrid can feel the lines blurring even as her powers seem to grow, until she must confront the truth about just how far some people, including herself, will go to keep the life they've always wanted . . ."--Amazon.